COVID-19 Place Confinement, Pro-Social, Pro-environmental Behaviors, and Residents’ Wellbeing: A New Conceptual Framework - Ramkissoon, Haywantee (Frontiers in Psychology, 2020)
Residents’ wellbeing in the present COVID-19 global health crisis requires a deeper understanding to determine appropriate management strategies to promote sustainable behaviors and contribute to human and planetary health. Residents’ behavior can have a profound influence in contributing to personal and global community’s health by responding effectively to emergency strategies in disease outbreaks such as the Coronavirus. It is evident that an understanding of residents’ behavior(s) pre COVID-19 across fields have relied on over-simplistic models, many of which will need to be revisited. Our interaction with people and nature while respecting social distancing has profound positive impacts on our physical, mental, emotional, and spiritual wellbeing. The current health pandemic has called that people be confined in their homes across many nations as a means to control the spread of the virus and save lives. This calls for research exploring the mechanisms; this paper develops and proposes a conceptual framework suggesting that place confinement promotes pro-social and household pro-environmental behaviors which could become habitual and contribute further to our people’s and our planet’s health. Some evidence shows that human connectedness to place may contribute to engagement in desirable behaviors. Interaction with other members of the household can help create meanings leading to collective actions promoting psychological wellbeing. Promoting hygienic behaviors in the household (frequent hand washing) while at the same time being conscious not to keep the water flowing when not required would contribute to a range of benefits (health, financial, biospheric, altruistic) and promote wellbeing. Engaging in pro-social behaviors may result in positive effects on psychological wellbeing, reducing mental distress giving rise to a sense of attachment and belongingness, trust and overall life satisfaction. Engaging people in low-effort pro-environmental behavior to maintain some levels of physical activity and biological harmony with natural environmental settings (e.g. gardening) may help reduce anxiety and distress. This is the first study exploring the interplay of relationships between place confinement, pro-social behavior, household pro-environmental behaviors, place attachment as a multi-dimensional construct and presenting their relationships to residents’ wellbeing. Behavioral change interventions are proposed to promote lifestyle change for people’s wellbeing and broader societal benefits.